LEGENDA CERITA RAKYAT ORANG KAYO HITAM SEBAGAI TRADISI LISAN DALAM PENULISAN SEJARAH LOKAL PADA PERIODE ISLAM DI KESULTANAN JAMBI - Triana Anur, Anggi; Heidi Karmela, Siti; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
The purpose of this research is to describe the Legend of the Orang Kayo Hitam as a historical source in the form of oral traditions and explain the historical values contained in the Legend of the Orang Kayo Hitam including religious, cultural and moral values. The method used in this research is a historical research method which consists of several stages, namely heuristics, criticism, interpretation and historiography. The primary sources used in this research were interviews with traditional elders, caretakers of the Tanjabtim Black Kayo people's cemetery, Jambi city residents. Meanwhile, secondary sources used are books, theses, journals and internet sources. The research results provide an explanation that the Legend of the Black Kayo People is a folk tale that has become an oral tradition in Jambi since the Islamic period until now, even the Black Kayo People today have become city icons such as the Keris Siginjei Monument, the name of the street, all of which are still tied to the Legend of the Black Kayo People. Apart from that, researchers also found that the legend of the Black Kayo People still has religious value and there are still many people who worship the Black Kayo People.